2016
DOI: 10.1080/1828051x.2016.1250128
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterisation of milk technological traits, protein fractions, and major mineral and fatty acid composition of Burlina cattle breed*

Abstract: The aim of the present study was to characterise milk of Burlina local cattle breed for traits of technological and nutritional relevance, such as milk coagulation properties (MCP), and protein, major mineral and fatty acid (FA) composition. Burlina is mainly reared in mountain areas of Veneto Region (Italy) and it has been inserted in conservation plans aiming to avoid biodiversity loss and marginal pasture areas abandonment. Eighty-one individual milk samples were collected in four farms. Milk coagulation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
11
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 35 publications
11
11
5
Order By: Relevance
“…Among MCPs, a 30 was the trait with the greatest CV, in agreement with results from other authors (Toffanin et al, 2015;Varotto et al, 2015;Niero et al, 2016). As expected, milk was richer in K and Ca, and poorer in Mg (Gaucheron, 2005;Soyeurt et al, 2009;Niero et al, 2016;Visentin et al, 2016Visentin et al, , 2018. However, among minerals, K concentration showed the lowest CV (8.61 %) and Mg the greatest one (17.59 %; Table 1).…”
Section: Descriptive Statistics and Correlationssupporting
confidence: 80%
“…Among MCPs, a 30 was the trait with the greatest CV, in agreement with results from other authors (Toffanin et al, 2015;Varotto et al, 2015;Niero et al, 2016). As expected, milk was richer in K and Ca, and poorer in Mg (Gaucheron, 2005;Soyeurt et al, 2009;Niero et al, 2016;Visentin et al, 2016Visentin et al, , 2018. However, among minerals, K concentration showed the lowest CV (8.61 %) and Mg the greatest one (17.59 %; Table 1).…”
Section: Descriptive Statistics and Correlationssupporting
confidence: 80%
“…This could explain the lower content of C14:0 and C16:0 in first lactation cows, as C14:0 and $50% of C16:0 are synthesised de novo in the mammary gland. Similar results were observed by Niero et al (2016) in Burlina breed, whose primiparous cows showed significantly lower levels of C16:0 and significantly higher levels of C18:1n9 with respect to cows of the other parities. Moreover, primiparous cows have on average lower rumen capacity and consequently lower dry matter intake and higher passage rate along the first two-thirds of the lactation, as well as lower capacity to adapt to the lactation diet (i.e.…”
Section: Effects Of Parity Number Lactation Stage and Seasonsupporting
confidence: 75%
“…This could have affected the levels of groups and individual FA across parity through a variation in the ruminal fermentation pattern toward a more acidogenic condition (Ramirez Ramirez et al 2016) leading to an increment of UFA, including both MUFA and PUFA. Again, a similar trend was observed in Burlina breed (Niero et al 2016) since the primiparous cows showed higher levels of UFA (29.96 vs an average of 27.12%) and MUFA (25.36 vs an average of 22.87%), and lower levels of SFA (69.72 vs an average of 72.78%) if compared to other parity cows. Primiparous cows are more susceptible to developing acidosis after parturition than multiparous cows (Krause & Oetzel 2006).…”
Section: Effects Of Parity Number Lactation Stage and Seasonsupporting
confidence: 57%
See 2 more Smart Citations